Active Living Program: sports and leisure in health promotion and quality of life of seniors in Petrolina and Juazeiro, Brazil - Nascimento, Marcelo (2017)
The Active Living Program, linked to the Physical Education course of the Universidade Federal do Vale do São Francisco (UNIVASF), aims to increase the physical and mental health levels of seniors in the cities of Petrolina Pernambuco (PE) and Juazeiro, Bahia (BA), Brazil, through regular physical exercise. Created in January 2015, with the support of MEC-PROEXT / 2015-2016, it provides free treatment to 165 elderly patients (aged 60-86 years), divided into 10 groups. Activities take place twice a week for 50 minutes in the following categories: Pilates, calisthenics, swimming, water aerobics, weight training and tennis. Before physical exercise, the elderly participate in 50 minutes of interdisciplinary activities, as follows: health lectures, psychosocial dynamics, art expression workshops and digital inclusion. The team consists of 45 Physical Education, Management, Visual Arts, Nursing, Pharmacy, Medicine, Psychology and Computer Science students, advised by 15 undergraduate professors. This program has been improving both the quality of life of seniors, and qualifying students in health at this university.